Relationship between Vitamin D AND IL6 in Convalescent Healthcare Workers with Covid-19 in Baquba Hospitals in Diyala Province - Maysam Abbas; Luma T. Ahmed; Mohammed A. Alkarkhi (Institute of Medico-legal Publications Pvt Ltd, 2022)
The outbreak of coronavirus disease 2019 (COVID-19) and pandemic, caused by severe acuterespiratory syndrome coronavirus 2 (SARS-CoV-2), has become a major concern globally. One hundredConvalescent HCWs patients with COVID-19 works in Diyala, Hospitals center, from October 2020 toMarch 2021 were included. We recruited 100 non-infected from healthy people and 100 PCR-confirmedinfected HCWs. In this review, we have summarized and discussed recent immunological studiesfocusing on the response of the host immune system, cytokine storms such as IL6 have been discussedas part of immunopathology mechanisms in SARS-CoV-2 infection. This may help us understandpatients’ immune status with COVID-19, particularly those with severe clinical presentation, and forma basis for further immunotherapeutic investigations. This study calculate that there is the relationbetween IL6 and Vitamin D3 in convalescent patients, accounting for a range of previously describedclinical predictors and, potentially directing future therapeutic strategies, including about Vitamin D.